Gender equality study on inheritance distribution in Gorontalo society - Ilyas, A. Sitti Kumala; Rais, Suardi; Samsuddin, Nurul Syazwana Binti; Jupri, Jupri; Cruz, Mawardi De La; Lamanasa, Muh. Syarif (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
In Gorontalo society, women often face challenges related to status, rights and roles in the context of inheritance. The differences in Islamic attitudes (law) towards men and women regarding the distribution of inheritance are not intended as discrimination and are not intended to glorify one and demean the other. However, what happens is that interpretations of religious texts often cause division and prolonged conflict when inheritance disputes are not resolved. The research method used is a phenomenological survey methodology to trace the practice of inheritance distribution in Gorontalo society, especially in Gorontalo City. This study uses primary and secondary data sources to ensure comprehensive research. The results of the study show that the gap in the distribution of inheritance that often occurs in Gorontalo society is the amount or portion received by male heirs with female heirs. This cannot be separated from the influence of three applicable inheritance law systems, namely customary inheritance law, Islamic inheritance law and inheritance law according to the Civil Code. Distribution is carried out based on customary law or state law is considered contrary to Islamic law, on the other hand when the distribution is carried out according to Islamic law it is considered unfair to female heirs. By examining inheritance practices from a gender equality perspective, we can reveal gaps or injustice in the distribution of inheritance, especially between male and female heirs, and provide a form of conflict mitigation through the concepts of Conflict Management and Conflict Transformation.